SISTEM KEAMANAN SEPEDA MOTOR BERBASIS FINGERPRINT - Lisa Fitriani Ishak (Universitas Muhammadiyah Tangerang, 2023)
AbstractAlong with the development of the era, the number of motorbikes in Indonesia has increased, resulting in the crime rate of motorcycle theft also increasing because it is not accompanied by a security system that is included on motorbikes. The purpose of this research is to create a reliable security system to monitor and secure motorbikes so that they can provide a sense of security to motorbike owners. This tool has control dimensions of 16 x 11 x 5.2 cm with the ESP8266 Wemos D1 R1 microcontroller connected to an internet connection making it an IoT system with data output on Google Spreadsheet. The sensor used is the FPM10A fingerprint sensor to identify motorcycle users' fingerprints as a 2 channel relay controller which functions as a replacement for the motorcycle ignition and ignition on the motorcycle, if the fingerprints do not match then the buzzer will light up to notify that the motorcycle is in a dangerous state. The fastest time required for the tool to turn on the motorcycle ignition with an average time of the test results at 1.05 seconds. The time to turn on the motorcycle ignition with an average time of the test results is 3.31 seconds. To turn off the motorcycle, the average testing time is 7.10 seconds, while the average buzzer testing time is 3.78 seconds. Utilization of Google Spreadsheet as a monitoring of motorcycle users by utilizing a third party as a server or a substitute for Google Form, namely by using the Pushing Box API. By registering 5 different fingerprints using the enroll program on the fingerprint sensor, the monitoring program can be carried out. IDs that have been recorded in Google Spreadsheet can be used as data for monitoring motorbike usage. Keywords: ESP8266 Wemos D1 R1, fingerprint FPM10A,Google Spreadsheet, Pushing Box APIAbstrakSeiring dengan perkembangan jaman jumlah sepeda motor di Indonesia meningkat mengakibatkan angka tindak kriminalitas pencurian sepeda motor meningkat juga karena tidak diiringi dengan sistem keamanan yang disertakan pada sepeda motor. Tujuan penelitian ini adalah membuat sebuah sistem keamanan yang handal untuk memonitor dan mengamankan sepeda motor sehingga dapat memberikan rasa aman kepada pemilik sepeda motor. Alat ini memiliki dimensi pada kontrolnya 16 x 11 x 5,2 cm dengan mikrokontroller ESP8266 Wemos D1 R1 yang dihubungkan dengan koneksi internet menjadikannya sistem IoT dengan keluaran data pada Google SpreadSheet. Sensor yang digunakan sensor fingerprint FPM10A untuk identifikasi sidik jari pengguna sepeda motor sebagai pengontrol relay 2 channel yang berfungsi sebagai pengganti kunci kontak sepeda motor dan ignition pada sepeda motor, apabila sidik jari tidak sesuai maka buzzer akan menyala untuk notifikasi bahwa sepeda motor dalam keadaan berbahaya. Waktu tercepat yang diperlukan alat untuk menyalakan kunci kontak sepeda motor dengan waktu rata-rata hasil pengujian pada 1,05 detik. Waktu untuk menyalakan ignition sepeda motor dengan waktu rata-rata hasil pengujian ada pada 3,31 detik. Untuk mematikan sepeda motor waktu pengujian rata-rata waktu ada pada 7,10 detik, sedangkan waktu rata-rata pengujian buzzer ada pada 3,78 detik. Pemanfaatan Google Spreadsheet sebagai monitoring pengguna sepeda motor dengan memanfaatkan pihak ketiga sebagai server atau pengganti Google Form yaitu dengan menggunakan Pushing Box API. Dengan mendaftarkan 5 sidik jari yang berbeda dengan menggunakan program enroll pada sensor fingerprint maka program monitoring tersebut dapat dilakukan. ID yang telah terdata dalam Google Spreadsheet dapat dijadikan data untuk monitoring penggunaan sepeda motor. Kata kunci : ESP8266 Wemos D1 R1, fingerprint FPM10A,Google Spreadsheet, Pushing Box API